2018
DOI: 10.1037/cou0000277
|View full text |Cite
|
Sign up to set email alerts
|

Socialization and well-being in multiracial individuals: A moderated mediation model of racial ambiguity and identity.

Abstract: Scholarly interest in racial socialization is growing, but researchers' understanding of how and when racial socialization relates to well-being is underdeveloped, particularly for multiracial populations. The present study investigated moderated mediation models to understand whether the indirect relations of egalitarian socialization to subjective well-being and self-esteem through integrated multiracial identification were conditional on phenotypic racial ambiguity among 383 multiracial adults. Tests of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Of the 15 studies we identified, nine focused on exploring and identifying factors that informed parents' use of this ethnic–racial socialization strategy (e.g., Cooper, Smalls‐Glover, Neblett, & Banks, ; Hagerman, ; Zucker & Patterson, ) and six examined the associations between messages of egalitarianism and youth outcomes (see Table ). As noted in Table , a majority found that egalitarianism promoted positive adjustment among youth (e.g., stronger integrated identity and higher self‐esteem [Villegas‐Gold & Tran, ]; higher academic expectations [Trask‐Tate, Cunningham, & Francois, ]); one study reported mixed findings (French, Coleman, & DiLorenzo, ), and one study reported null findings (White‐Johnson, ). D. L. Hughes et al () noted that, in their own work with diverse ethnic–racial groups, messages of egalitarianism were among the most frequent types of socialization reported; however, our review revealed that this is the least empirically studied type of socialization, and there is an insufficient literature base from which to draw conclusions regarding its potential consequences for youth adjustment (see Table ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…Of the 15 studies we identified, nine focused on exploring and identifying factors that informed parents' use of this ethnic–racial socialization strategy (e.g., Cooper, Smalls‐Glover, Neblett, & Banks, ; Hagerman, ; Zucker & Patterson, ) and six examined the associations between messages of egalitarianism and youth outcomes (see Table ). As noted in Table , a majority found that egalitarianism promoted positive adjustment among youth (e.g., stronger integrated identity and higher self‐esteem [Villegas‐Gold & Tran, ]; higher academic expectations [Trask‐Tate, Cunningham, & Francois, ]); one study reported mixed findings (French, Coleman, & DiLorenzo, ), and one study reported null findings (White‐Johnson, ). D. L. Hughes et al () noted that, in their own work with diverse ethnic–racial groups, messages of egalitarianism were among the most frequent types of socialization reported; however, our review revealed that this is the least empirically studied type of socialization, and there is an insufficient literature base from which to draw conclusions regarding its potential consequences for youth adjustment (see Table ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…Despite their many strengths, these studies are limited by their measurement of racial-ethnic socialization. Three studies used only one item (Brown et al, 2007; Csizmadia et al, 2014; Lesane-Brown et al, 2010), and one study used an unvalidated measure created for the study (Villegas-Gold & Tran, 2018). The last three studies (Brittian et al, 2013; Chong & Kuo, 2015; Gonzalez et al, 2006) used the Familial Ethnic Socialization Measure (Umaña-Taylor, 2001; Umaña-Taylor, Fine & The Umaña-Taylor, 2004), which only focuses on ethnic and cultural socialization and was designed for studying monoracial minority families.…”
Section: Validation Of the Multiracial Youth Socialization (My-soc) S...mentioning
confidence: 99%
“…Brittian et al (2013) found a positive relationship between family ethnic socialization and ethnic identity exploration and resolution among Latinx-White and Asian-White Multiracial college students. Another study found a positive correlation between egalitarian socialization, or messages promoting appreciation of all racial groups, and the degree to which Biracial college students felt their racial identities were integrated (Villegas-Gold & Tran, 2018). Chong and Kuo’s (2015) study with Asian-White Biracial participants noted frequency of Asian socialization was highest among those in the Asian-White integrated identity profile, while White socialization was highest among those in the White dominant identity profile.…”
Section: Validation Of the Multiracial Youth Socialization (My-soc) S...mentioning
confidence: 99%
“…Existing studies of cultural socialization among multiracial families have typically assessed parental messages and practices (e.g., Brittian, Umaña-Taylor, & Derlan, 2013;Jackson, Wolven, & Crudup, 2017;Rollins & Hunter, 2013;Villegas-Gold & Tran, 2018), similar to studies of monoracial families (Yasui, 2015). A limitation of this approach is that it only captures aspects of cultural socialization that can be directly observed by youth or that parents are consciously aware of (Yasui, 2015).…”
Section: Cultural Socialization In Multiracial Familiesmentioning
confidence: 99%